Labelling and Information Schemes for the Circular Economy - Laubinger, Frithjof (OECD Environment Working Papers, 2021)
Circular Economy Labels and Information Schemes (CELIS) compose the group of labels, certifications, standards of information schemes that fully or partially address one or more resource efficiency or circular economy elements. CELIS can play an important role in fostering circular economy activities. They can empower market actors to distinguish and discriminate products based on environmental performance, which stimulates market development and innovation in resource efficient products and services. Information systems also enable better supply chain management and allow firms to identify environmental impacts and risks in their supply chains. This paper provides an overview of the current CELIS landscape, assesses the drivers and barriers to a greater uptake of business-to-business information systems, and identifies circular economy aspects that are underdeveloped in the existing consumer labels landscape